CLINICAL AND LABORATORY FEATURES OF MEASLES MENINGITIS AND MENINGOENCEPHALITIS IN ADULTS - Golub, A.P.; Duda, O.K.; Sukhov, Yu.O. (World of Medicine and Biology, 2020)
The purpose of our study was to systematize and analyze the clinical and laboratory features of measles meningitis and meningoencephalitis in adults who were inpatient treatment at the Kiev City Clinical Hospital No. 4 in the period 2006-2019. We examined 37 adult patients with measles complicated by meningitis or meningoencephalitis. Among the examined patients, there were 54% men (n=20) and 46% women (n=17). Young people aged 18 to 40 years prevailed (86.5%) among all the examined patients. Despite the fact that these measles complications are observed quite rarely, 0.5-1 per 1000 cases of the disease, their development aggravates the course of the disease, lengthening the duration of hospital stay. The nature of the central nervous system disorders statistically significantly depended on the time of patients’ admission to the hospital (χ2=6.84, φ=0.43, p=0.009). Upon admission to the hospital, all patients had positive meningeal symptoms, which required a therapeutic and diagnostic lumbar puncture. Obtained results of the cerebrospinal fluid analysis showed the presence of lymphocytic pleocytosis was determined from 15 to 230 cells in 1 μl, which indicated a different degree of severity of the inflammatory process, which depended on the nature of the central nervous system disorders.